Lymphadenopathy after the third Covid-19 vaccine - Can Özütemiz (Elsevier, 2021)
Summary: Axillary lymphadenopathy ipsilateral to the vaccination site has been clinically and radiologically reported after administration of COVID-19 vaccines. This can be an important diagnostic dilemma, particularly in cancer patients who are being staged or re-staged, as this benign entity may mimic metastasis, cause unnecessary biopsies and changes in therapy. Here we present a breast cancer patient and a patient with squamous cell carcinoma of the head and neck, who had already received the first two doses of mRNA type COVID-19 vaccines before, now presenting with new hypermetabolic reactive lymphadenopathy on FDG PET/CT after the third booster dose.